SIFAT-SIFAT PENYALAAN BRIKET DENGAN MENGGUNAKAN SERBUK GERGAJIAN KAYU DENGAN COCO DUST SEBAGAI PEMANTIK - Petrus Patandung (Jurnal Penelitian Teknologi Industri, 2016)
ABSTRACTThe properties of wood sawdust with coco dust for briquetting has been implemented. The purpose of this research product dinyalahkan briquettes obtained easily by using the "coco dust" as material lighter or startup. The research method uses a form of graphs and data were analyzed descriptively. The results of analysis of the experiments using charcoal briquettes burning waste wood sawdust. Results of experiments with burning briquettes parameters: Ignition long to ashes 98.63 to 100.65 minutes; old startup from 0.04 to 0.09 minutes until the resulting fire and smoke generated / smoke lost 10.15 to 18.13 minutes. For the boiling water using charcoal briquettes of wood sawdust using the time from 20.30 to 24.68 minutes and using charcoal briquettes as much as 101.68 to 102.90 g. Charcoal briquettes of wood sawdust parameters moisture content from 4.47 to 4.95%, from 5.14 to 7.03% ash; mengup combustible material at a temperature of 950 ° C 4.02 to 5.13% and a calorific value of 2220-3862 cal / g. Keywords: sawn briquettes, coco dust, ignition